The use of generative AI tools in design work: Motivation and decision-making process of users - Kim, Jhonghee; Kim, Hyungjoon (Edelweiss Applied Science and Technology, 2025)
As generative AI technologies evolve, more designers are integrating these tools into their workflows. While existing research has examined the use of generative AI in design, few studies have conceptualized user engagement within an integrated model of motivational and behavioral factors. This study explores key constructs—attitudes, subjective norms, perceived behavioral control, intention to use, and actual usage—through the Uses and Gratifications Theory (UGT) and the Theory of Planned Behavior (TPB). Results indicate that designers’ attitudes and subjective norms significantly affect their intention to adopt generative AI tools, which in turn influences actual usage. Designers generally hold positive attitudes toward these tools, and external social influences are crucial to their adoption. Finally, enhancing perceived control may further promote adoption and integration into design practices.